Cormac McCarthy’s "The Road": Language and Memory in Post-Apocalyptic Fiction - Davlatovna, Hayitova Nadejda; O'ktamovna, Yusupova Hilola (International Journal on Integrated Education, 2023)
In an age of existential turmoil, post-apocalyptic fiction envisions a depopulated world—a world ravaged by war, plague, ecocide, or cosmological judgments. Often times, it is mankind's own hand that strikes. But the story doesn't end there. Because the post-apocalyptic world is often a place of survival and afterlife, nothing like the bleak wasteland of Cormac McCarthy's The Road (2006). Set in a world ravaged by an unnamed cataclysm, the novel examines the ecological, psychological, and sociological changes that take place after the apocalypse. Just as the "before" world is replaced by the "after" world, the memory of the past should be replaced by the beginning of the future. But just as we cannot write outside language, we cannot write outside past and memory. As much as they attempt to portray a lifeless world, post-apocalyptic fiction, against its will, evokes memories, undoes the end, and brings new life to life. Even post-apocalypse can't be the end of the story because it's ultimately a story itself.